(untitled) (Journal of Economic Research & Business Administration, 2024)
This article explores the issue of vehicle efficiency based on its technical characteristics. The aim of the study is to identify the most important technical parameters affecting the efficiency of road transport. The direction of scientific research was to determine the optimal characteristics of the car to achieve maximum efficiency. Maintenance takes an important place in the operation of vehicles, and is also aimed at reducing risks during transportation, since unplanned stops due to repairs can disrupt delivery times. The importance of the work lies in determining methods for calculating the efficiency of vehicles based on their technical characteristics. The methodological basis of the study is a comprehensive system of scientific methods used in the study of the subject of research. The main result of the research work was the definition of a method that allows you to choose a car that will be more efficient during operation for transporting cargo. It is proposed to break down the cars by makes and models, indicate the range at the start of work in the year, the planned weight and mileage. The obtained information makes it possible to determine the number of repairs between runs and the possibility of determining the need for overhaul of the vehicle. While the vehicle is under repair, its productivity decreases accordingly. The value of this study lies in determining the ability to choose a vehicle taking into account its technical characteristics, the frequency of maintenance, which ultimately affects the performance of vehicles, and for the company to generate income. The practical significance of the results of the work done is due to the fact that transport companies, which take full responsibility for transportation, can practically apply the results of this study and determine more efficient vehicles, based on the fact that the company’s fleet is often worn out. Key words: transportation, logistics, modeling, maintenance, efficiency.